Safety and therapeutic potential of allogeneic adipose-derived stem cell spray transplantation in ischemic cardiomyopathy: a phase I clinical trial - Takuji Kawamura; Daisuke Yoshioka; Ai Kawamura; Yusuke Misumi; Takura Taguchi; Daisuke Mori; Shunsuke Saito; Takashi Yamauchi; Hiroki Hata; Shigeru Miyagawa (Journal of Translational Medicine)
Abstract Background Ischemic cardiomyopathy, characterized by coronary artery atherosclerosis, impairs the myocardial tissue. Coronary artery bypass grafting (CABG) is commonly used to revascularize affected areas and improve patient survival rates; however, it can fail to enhance cardiac function. Impaired capillary blood flow may obstruct functional recovery, prompting interest in treatments, such as angiogenic factor administration. Adipose-derived stem cells (ADSCs), which are known for immune evasion, have shown the potential to construct capillary networks and improve myocardial function. This clinical trial aimed to evaluate the safety and efficacy of ADSC spray therapy combined with CABG. Methods This single-center, randomized, double-blind study involved patients with ischemic cardiomyopathy who were scheduled for CABG and who had a left ventricular ejection fraction ≤ 40%. The participants were randomized to receive CABG as well as ADSC spray therapy or placebo. The primary endpoints were safety, changes in late gadolinium-enhanced (LGE) magnetic resonance imaging (MRI) volumes, and feasibility. The secondary endpoints included left ventricular function, exercise tolerance, and heart failure symptoms. Results Seven patients were enrolled; of them, six were randomized to receive ADSC therapy (n = 3) or placebo (n = 3). The procedure was successfully completed with minimal adverse events. One patient in the ADSC group developed pleural effusion that was resolved with drainage. The LGE-MRI volumes decreased in the ADSC group but remained unchanged in the placebo group. Improvements in left ventricular function and exercise tolerance were noted in the ADSC group, with heart failure symptoms improving to New York Heart Association class I. In contrast, the placebo group showed no significant changes, with one patient experiencing worsening symptoms. Conclusions ADSC spray therapy combined with CABG demonstrated safety and efficacy at enhancing cardiac function. ADSC likely contributes to capillary network reconstruction, thereby augmenting the benefits of CABG. Future phase II and III trials are warranted to confirm its therapeutic efficacy and long-term outcomes. This novel approach represents a significant advancement in the treatment of ischemic cardiomyopathy and offers a viable strategy for improving myocardial function and patient prognosis. Trial registration This study was registered with the Japan Registry of Clinical Trials (jRCT2053190103) and ClinicalTrials.gov (NCT04695522) Graphical Abstract